2019
DOI: 10.1093/icesjms/fsz238
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting for recreational fisheries management: a derby fishery case study with Gulf of Mexico Red Snapper

Abstract: In a derby fishery, anglers race to catch as many fish as possible during a limited season. To meet legal mandates to prevent overfishing, forecasting accuracy is paramount. Red Snapper is among the most prized species in the US Gulf of Mexico and represents a politically charged derby fishery case study. We describe the management considerations, data, methods, and specialized statistical forecasting approaches used to estimate recreational component season lengths to maximize fishing opportunities while meet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…In 2005, the Gulf Council established a new rebuilding plan for red snapper, which included dramatically reduced catch limits, a recreational bag limit, a commercial individual fishing quota program, and controls on shrimp trawl fishing effort to reduce red snapper bycatch. Since the implementation of these additional management measures, red snapper fishing mortality has been reduced to levels below the limit set by managers, the stock size has increased, and the average size in the catch has doubled (Farmer et al, 2020). As of 2018, the stock had not yet recovered to its optimal population size but was considered no longer overfished or undergoing overfishing, and red snapper had repopulated much of the West Florida Shelf where it had previously been heavily overexploited (SEDAR, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In 2005, the Gulf Council established a new rebuilding plan for red snapper, which included dramatically reduced catch limits, a recreational bag limit, a commercial individual fishing quota program, and controls on shrimp trawl fishing effort to reduce red snapper bycatch. Since the implementation of these additional management measures, red snapper fishing mortality has been reduced to levels below the limit set by managers, the stock size has increased, and the average size in the catch has doubled (Farmer et al, 2020). As of 2018, the stock had not yet recovered to its optimal population size but was considered no longer overfished or undergoing overfishing, and red snapper had repopulated much of the West Florida Shelf where it had previously been heavily overexploited (SEDAR, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Compounding the problem, a 2014 federal court ruling requiring greater accountability measures in the fishery led to the implementation of more conservative annual catch targets. In subsequent years, recreational fishing seasons in federal waters were as short as 3 to 4 d. However, studies of angler behavior revealed that the shorter seasons did not proportionally reduce catches, instead promoting “derby‐style fishing” and worsening perceptions of angler dissatisfaction (Powers and Anson 2016; Farmer et al 2019). In recent years, recreational season lengths have been extended and landings for Red Snapper have been at all‐time highs, collectively providing a major source of concern and conflict within the fishery.…”
mentioning
confidence: 99%
“…These spatial indices, along with probability maps of released CPUE hotspots, suggest that the Abrolhos Islands are an isolated case where there is potential scope for targeted spatial management, given individual reporting of access to the fishery at the Abrolhos Islands is mandatory. An example of this type of management challenge can be seen in the Gulf of Mexico, where the declining health of the red snapper fishery is attributed to the derby-style behaviour of fishers, where they compete to attain high harvest levels before seasonal closures (Hackett et al 2005;Smith et al 2009;Farmer et al 2020). Bag limits and seasonal closures alone have proven ineffective for a derby-style fishery, as effort compression can lead to higher CPUE, resulting in high released CPUE.…”
Section: Discussionmentioning
confidence: 99%